Methodologies for measuring the quality of urban infrastructure for pedestrian mobility: A systematic literature review - Marangão, Glaucia Hellen de Freitas; Magagnin, Renata Cardoso; Fontes, Maria Solange Gurgel de Castro; Azambuja, Maximiliano dos Anjos (Revista Nacional de Gerenciamento de Cidades, 2022)
The spatial quality of urban infrastructure for pedestrian mobility, influenced by the physical aspects of space and the elements perceived by pedestrians, can induce the behavior of people in order to encourage or inhibit the use of some routes. Therefore, identifying methods and techniques to evaluate this infrastructure’s quality is important to contribute to the analysis and diagnosis, which are fundamental for urban management. Given this context, this article aims to identify, through a systematic literature review , the main methods and techniques for evaluating the spatial quality of sidewalks from the micro, meso and macro scales. The Scopus platform database was used and the search delimited the period from 2016 to 2020 for scientific articles. The analysis of 42 articles allowed us to identify: (1) their main characteristics (most relevant authors evaluating this theme, countries where the study was carried out, year of the research´s development and journals with the highest number of publications on this theme, among other general aspects), (2) the main methodologies and techniques for the evaluation of spatial quality, and (3) the importance of the scale of analysis to evaluate urban infrastructure for pedestrian mobility and its influence on the analyses of the results.